HILO training improves performance in elite runners - Stray-Gundersen, J.; Chapman, J. R.; Levine, B. D. (Medicine & Science in Sports & Exercise, 1998)
One week after the US national track and field championships 26 athletes (M = 17; F = 9) who had competed there entered a 27 day altitude training camp. They ran 3,000-m time trials and did laboratory testing at sea level before and after the camp. Blood was measured prior to the camp, 20 hours after ascent, 19 days after ascent, and 20 hours after return to sea level. The camp consisted of living at moderate altitude (2,500 m) and performing interval training at 1,250 m and base training at both 1250 and 3,000 m. EPO increased 92% within 20 hours of exposure but returned to close to normal by day 19. On return to sea level hemoglobin increased from 13.2 to 14.3 gm/dl, hematocrit increased by 4%, and arterial oxygen content increased by 8%. VO2max increased from 71.6 to 73.7 ml/kg/min while 3,000-m time improved from 8:45 to 8:39+. This study contained no control group, such as a live and train low group and these phenomena could be due to any number of reasons that affect performance, one being that 3,000 m might not have been the event for which trained states were attained at the national championships. Implication: Another assertion that living high and training low improves sea level performance in endurance runners but the study's design does not allow one to put much faith in this finding.